ANALISIS FINANCIAL DISTRRESS DENGAN METODE ZAVGREN UNTUK MEMPREDIKSI KEBANGKRUTAN PT BUKALAPAK.COM TBK - Pandita, Zera Athalia; Hasanah, Nurul (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The growth of internet users has driven the expansion of e-commerce in Indonesia. However, this increase in internet users is not reflected in PT Bukalapak.com Tbk, which appears to be experiencing financial distress. This study aims to predict the potential bankruptcy of the e-commerce company PT Bukalapak.com Tbk using the Zavgren and Grover methods. The data used in this research is secondary data obtained from PT Bukalapak.com Tbk's financial statements for the years 2021-2023, which have been published by Bukalapak. The method employed in this study is quantitative descriptive analysis. The population of the study consists of PT Bukalapak.com Tbk during the 2021-2023 period, with a total sampling method used for the sample. The results of this study indicate no significant difference between the Zavgren and Grover methods in predicting the bankruptcy potential of PT Bukalapak.com Tbk. Based on the results of the Zavgren method, it shows that PT Bukalapak.com Tbk has the potential to go bankrupt in Q1 and Q4 of 2021. Meanwhile, based on the results of the Grover method, it shows that PT Bukalapak.com Tbk is in the healthy category throughout 2021-2023. This research provides PT Bukalapak.com Tbk with valuable insights and evaluations related to the company's management